PERENCANAAN SISTEM PERINGATAN DINI BENCANA TANAH LONGSOR DI DUSUN LUCU PALONGAN DESA CAMPOAN KECAMATAN MLANDINGAN KABUPATEN SITUBONDO JAWA TIMUR - Mukhlis, Teuku; Fathani, Teuku Faisal; Sudarno, Ign. (Civil Engineering Forum Teknik Sipil, 2008)
Lucu Palongan Sub-village is located at hills terrain which is critically prone to soil mass movement due to the morphological characteristic of plateu with steep slopes in addition to geological setting of volcanic breccia bedrock covered by colluvial sediments. The research is initiated by soil mass movement occurrence in Lucu Palongan Sub-villag. It is situated in community’s farm land which is a typical ground faulting with soil cracks subsided by 3 meters at the crown area. The study is conducted to identify the causal factors and mechanism of soil mass movement, to observe the condition of the affected areas and society, to discover the areas vulnerable to landslide effects and to plan early warning system for landslide disaster. The primary data for the research is gathered from field investigation. Analysis on the slope stability is carried out by employing SLOPE/W program. The study identifies that soil mass movement in Lucu Palongan Sub-village is a typical slide. The causal factors of soil mass movement at the researched areas are the farm lands existed on the slopes causing water on land surfaces accumulated, thence the intensity of water slipping into subsurface increases, shear strength of soil significantly diminishes due to saturation. The most vulnerable areas to landslide are Bretan and Batuampar Sub-village of Selowogo Village. The indications of soil mass movement were initially noticed by the residents of Lucu Palongan Sub-village through landslide monitoring instrument. Afterward, the information was communicated to the people of Bretan and Batuampar Sub-village.